Analisis Kesalahan Siswa Dalam Memecahkan Masalah Matematika Higher Order Thinking Skills (HOTS) Berdasarkan Kriteria Hadar Ditinjau Dari Kemampuan Awal Siswa - Erwinda Gracya Laman; Suradi; Asdar (Issues in Mathematics Education (IMED), 2019)
This study aims to know the description of students' error in solving Higher Order Thinking Skills (HOTS) mathematical problems and the description of errors differences of geometry based on Hadar criteria. This type of research is descriptive research using qualitative approach. Retrieval of the subject is performed by providing prior knowledge test of grade XII MIPA 3 , then from the result of thetest selected 6 subjects based on existing categories. The instrument used in this research are prior knowledge test which contains 30 number of multiple choices, written tests of Higher Order Thinking Skills which contains 2 number of essay and interview guidelines. Errors are analyzed by using the Hadar error category which consists of 6 errors. The results of this research show that based on the Hadar error criteria, errors that occur are misused data, misinterpreted language, logically in valid inference, distorted theorem or definition, unverified solution, and technical error. Subjects who solving HOTS mathematics problem of geometry tend to make logically invalid inference, distorted definition or theorem, and technical errors. The results of this research are expected to add insight about the types of errors made by the students of senior high school in geometry topic, especially in solving higher order thinking skills problems so that the mistakes can be immediately minimized in the process of learning.